The antitoxicity effects of Parkinsonia aculeate against scorpion venom (Buthotus saulcyi): in vivo and in vitro studies - A Jalali; H Vatanpour; M Bagheri Khalili; M Ayatollahi; M Kamalinejad (Institue of Medicinal Plants, ACECR, 2006)
Background: Currently, traditional medicine has received much attention. Accumulating evidence in Iranian folk medicine shows Parkinsonia aculeate are used as a folk remedy in scorpion envenomation. Objective: Based on this and search for an alternative treatment in scorpion sting, the pharmacologic and immunologic effects of hydroalcoholic extract of Parkinsonia aculeate leaves were studied in scorpion sting through in vivo and in vitro methods. Results: Obtained results from in vitro pharmacological study using chick biventer cerivicies (CBC) preparation, show that hydroalcoholic extract of plant has a partial agonistic properties on cholinergic receptors and act as competitive antagonist in presence of exogenous acetylcholine. Furthermore, the pharmacologic results revealed extract has not significant effects on neutralization of neuro-muscular transmission outwards due to Buthotus saulcyi scorpion venom effects. These results were confirmed by in vivo study which plant extract has not significant consequences to delay death time mean of one LD50 scorpion venom vein injection or block death of mice. As well, Gel diffusion study shows no immunologic reaction between plant extract and 4 known hazardous scorpion species of Iran. Conclusions: As a consequence, this study indicates that the use of Parkinsonia aculeate not to be considered as protective antidote or a true remedy for clinical outwards following scorpion bites.